Marx, Marginalism and Modern Sociology - Clarke, Simon. author. aut Link
IX, 339 p.
Keywords: Marx, Marginalism and Modern Sociology offers an original interpretation of Marx's critique of political economy as the basis of a critique of modern economics and sociology. The core of the book is an account of Marx's theory of alienated labour as the basis of Marx's work as a whole. The critical implications of this theory are developed through an analysis of the historical development of liberal social theory from political economy to the modern disciplines of economics and sociology.